Thromboelastography versus standard coagulation testing in the assessment and reversal of coagulopathy among cirrhotics: a systematic review and meta-analysis. Issue 3 (March 2020) - Kovalic, Alexander J.; Khan, Muhammad Ali; Malaver, Diego; Whitson, Matthew J.; Teperman, Lewis W.; Bernstein, David E.; Singal, Ashwani; Satapathy, Sanjaya K.
Abstract : The utility of thromboelastography/thromboelastometry currently has unvalidated clinical benefit in the assessment and reversal of coagulopathy among cirrhotic patients as compared to standard coagulation testing. A novel systematic review and meta-analysis was conducted in order to assess pooled outcome data among patients receiving thromboelastography/thromboelastometry as compared to standard coagulation testing. As compared to standard coagulation testing, there was a significant reduction in the number of patients requiring pRBC, platelet, and fresh frozen plasma transfusions among thromboelastography/thromboelastometry group with pooled OR 0.53 (95% CI 0.32–0.85; P = 0.009), 0.29 (95% CI 0.12–0.74; P = 0.009), and 0.19 (95% CI 0.12–0.31; P < 0.00001), respectively. Similarly, there was a significant reduction in number of pRBC, platelet, and fresh frozen plasma units transfused in the thromboelastography/thromboelastometry group with pooled MD −1.53 (95% CI −2.86 to −0.21; P = 0.02), −0.57 (95% CI −1.06 to −0.09; P = 0.02), and −2.71 (95% CI −4.34 to −1.07; P = 0.001), respectively. There were significantly decreased total bleeding events with pooled OR 0.54 (95% CI 0.31–0.94; P = 0.03) and amount of intraoperative bleeding during liver transplantation with pooled MD −1.46 (95% CI −2.49 to −0.44; P = 0.005) in the thromboelastography/thromboelastometry group. Overall, there was no significant difference in mortality between groups with pooled OR 0.91 (95% CI 0.63–1.30; P = 0.60). As compared to standard coagulation testing, a thromboelastography/thromboelastometry-guided approach to the assessment and reversal of cirrhotic coagulopathy improves overall number of patients exposed to blood product transfusions, quantity of transfusions, and bleeding events. Abstract : Supplemental Digital Content is available in the text.